The effectiveness of e-textiles in providing thermal comfort: A systematic review and meta-analysis. Issue 7 (April 2023) - Lee, Ching; Tan, Jeanne; Lam, Ngan Yi Kitty; Tang, Hiu Ting; Chan, Hui Haang
Thermal electronic textiles (e-textiles) are increasingly common in the market and aim to provide thermal comfort in cold environments. Currently, however, there is a paucity of information on the relative effectiveness of the different types of thermal e-textile. This study sets out to compare the effectiveness of a range of such textiles reported in the relevant literature. The study addresses the issue of heating effectiveness in terms of gender and particular body regions. Among the results reported, three primary categories emerged for investigation: (a) metabolic response, comprising metabolic rate and heart rate; (b) respiratory response i.e. mean skin temperature; and (c) perceptual response, including thermal sensation and comfort sensation. Eight eligible studies with a total of 83 subjects aged 23.4 ± 1.49 years, 40.96% male and 37.35% female and 21.69% in which gender was not reported, were investigated for the meta-analysis. Results show a significant improvement in changes in mean skin temperature and thermal sensation between the control and experimental groups via heating intervention ( p < 0.05), but results were not significant for changes in metabolic rate, heart rate, and comfort sensation ( p > 0.05). Regarding gender, thermal e-textiles significantly enhanced the changes in mean skin temperature in males and thermal sensation in both males and females ( p < 0.05). With regard to different body regions being heated, there were significant effects on changes in mean skin temperature, thermal sensation, and comfort sensation in heating the upper torso ( p < 0.05) and on changes in thermal sensation in heating the feet and toes ( p < 0.05). The results reported here may serve as reference points for the further development of smart heating textile technology.